Discriminative power of the health status questionnaire 12 in relation to age, sex, and longstanding illness: findings from a survey of households in Great Britain. Issue 5 (October 1997) - Bowling, A; Windsor, J
Abstract : STUDY OBJECTIVE: To assess the ability of the health status questionnaire 12 (HSQ-12) to discriminate between older and younger age groups, its appropriateness for use with an older population in terms of the spread of responses across categories, floor or ceiling effects, and its ability to discriminate between those with and without a reported longstanding illness and type (sensitivity and specificity). DESIGN AND SETTING: The vehicle for the study was the Office for National Statistics (ONS) omnibus survey in Great Britain. The sampling frame was the British post-code address file of "small users", stratified by region, and socioeconomic factors. This file includes all private household addresses. The postal sectors were selected with probability proportional to size. Within each sector 30 addresses were selected randomly. The number of selected addresses was 3000. PARTICIPANTS: Altogether 1912 adults aged 16 and over were interviewed in person in their own homes, giving a response rate of 72%. MEASURES: The HSQ-12, and the ONS general household survey questions on longstanding illness; the ONS omnibus standard sociodemographic items. MAIN RESULTS: There were exceptionally high rates of item response in all age groups. The score differences by construct (e.g., age group, sex, longstanding illness) were in the expected directions with statistically significant age gradients. Age was associated with most of the HSQ-12 domains, although this association had interactions with longstanding illness or sex. The differences in HSQ-12 scores with reported longstanding illness and type of longstanding illness made theoretical sense, which supports the discriminative power of the scale. The frequency distributions for HSQ-12 items in relation to age and sex, and by reporting of longstanding illness are also presented here in order to demonstrate ceiling effects. Most respondents in all age groups achieved high (good) scores on the "social functioning" subscale. The HSQ-12 had good results for specificity when tested against reporting of a longstanding illness, although this was at the expense of sensitivity. CONCLUSIONS: The results support the use of the HSQ-12 with older populations, particularly for those with chronic illnesses, although it will reveal relatively few problems among younger populations. The results presented here indicate that it will require supplementation with more sensitive disease and/or domain specific scales in the areas of interest or intervention, but it provides an acceptable, brief, core measure of health related quality of life. This paper present the first British normative data using the HSQ-12.